Pengaruh Tingkat Pendidikan, Pengetahuan Keuangan, dan Perencanaan Keuangan terhadap Perilaku Keuangan pada Pelaku UMKM Desa Teluk Samak Kabupaten Kepulauan Meranti - Gustina, Arosa; Ibrahim, Mariaty (Economic Reviews Journal, 2024)
In general, MSMEs in the Indonesian economy have a crucial role in economic activities such as the largest contributor to employment, the main role in local economic development and citizen empowerment, forming new markets and sources of innovation, and contributing to the balance of payments. The scientific methodology utilized in this study is quantitative. Area This exploration was directed in Teluk Sama Town, Rangsang Locale, Meranti Islands Rule, Riau Region. The justification for picking this area is on the grounds that it has never been investigated. The Likert scale was used as the method of measurement in this study. The populace in this study is all MSME entertainers in Teluk Samak Town, Meranti Islands Rule upwards of 35 MSMEs. The information assortment methods utilized in this study utilized surveys and meetings. In the variable level of education, the results were shown that the level of education in MSME actors in Teluk Samak Village, Meranti Islands Regency as a whole was in the very good category. This is because the level of education possessed by MSME actors in Teluk Samak Village, Meranti Islands Regency as a whole is very good. In the financial knowledge variable, results were obtained which showed that financial knowledge in MSME actors in Teluk Samak Village, Meranti Islands Regency was in the good category. In the financial planning variable, results were obtained which showed that financial knowledge in MSME actors in Teluk Samak Village, Meranti Islands Regency was in the good category. In the financial behavior variable, results were obtained which showed that financial behavior in MSME actors in Teluk Samak Village, Meranti Islands Regency was in the Very Good category. Persial should be visible that the variable degree of instruction impacts monetary way of behaving. Persial should be visible that monetary information factors impact monetary way of behaving. Persial can be realized that monetary arranging factors impact monetary way of behaving. At the same time, it very well may be seen that the factors of instruction level, monetary information, and monetary arranging impact monetary way of behaving.